Theoretical study of the structural, electronic structure, fermi surface, electronic charge density and optical properties of the of LnVO4 (Ln= Sm, Eu, Gd and Dy) - Ali Hussain, Reshak, Prof. Dr. (Electrochemical Science Group (ESG), 2014)
Link to publisher's homepage at http://www.electrochemsci.org/